AKTUALISASI MAKNA SYARÎ’AH DAN FIQH DALAM KONSEP HUKUM ISLAM - Bustami Saladin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
Islamic law is in accordance with its dimension in a history, thatmakes the content of the study in its dimension always appearsany system or method. That’s why in Rasulullah saw era,Islamic law is based on Allah swt’s revelation and Rasulullah’sjudgment, namely, Islamic law in Alquran and Sunnahperspectives. The purpose of declaring Islamic law is applyingand protecting the benefit for people. It is applied in Islamic lawthat concerns all aspects of human life that has three aspects:dharûriyah (primary), hajiyah (secondary), and tahnisiyah(complementary).